HUBUNGAN INDEKS MASSA TUBUH, DURASI KERJA, DAN BEBAN KERJA FISIK TERHADAP KEBUGARAN JASMANI KARYAWAN KONSTRUKSI DI PT. X - Fiqih Naila Fikar; Suroto Suroto; Baju Widjasena (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Physical fitness associated with a person's ability to perform daily work efficiently without causing fatigue. Physical fitness was good impact on work productivity is good for the employees and the company. The impact of the lack of physical fitness for employees can be a decline in productivity, turnover, human error, and absenteeism improvment.The purposive in this study was to analyze the relationship of body mass index, duration of employment, and physical workload on the physical fitness of employees at PT. X 7 Floor Building Project and Infrastructure Hospital Y. This study used a cross-sectional analytical observational with approach in this study as many as 35 employees. The number of samples used as many as 31 employees PT.X purposive sampling method using inclusion criteria employees who are willing to become respondents, male sex, and who have sistoli blood pressure (<140 mmHg) and diastolic blood pressure (<90 mmHg). Data were collected by using a sheet of respondents, observation, and Harvard step test 3 minutes. The Result univariate analysis obtained most workers age 26-35 years (41.9%). Education level educated employees SMA / SMK and D3 / S1 equally (41,%). Work Period> 5 years (61.3%). Physical fitness is less (45.2%). Body mass index normal employees (51.6%). Working Length employees> 8 hours (77.4%). Physical Workload mild (83.9%). Statistical test using rank spearrman relationship. Results showed There was no association between body mass index invitation physical fitness (pvalue = 0.789), there was no correlation between the duration of the work with physical fitness (pvalue = 0.399), there was no correlation between physical workload with physical fitness (pvalue = 0.081). Safety Officer will need to provide safety sharing the importance of maintaining physical fitness.